Study of the quality of Hermeneutic phenomenology studies in nursing - Mohsen Adib-Hajbagheri; Shahnaz Bolandianbafghi (Kurdistan University of Medical Sciences, 2018)
Background & Aim: The number of nursing researchers who use phenomenology studies and especially hermeneutics in their research is increasing. The validity of these studies has always been sought by researchers to judge the accuracy of the research, the methods of study and its findings. Therefore, in this study, the quality of Hermeneutic phenomenology studies in nursing was investigated. Materials & Methods: This study is a descriptive study conducted through extensive search of Proquest, PubMed, Web of Science and Scopus databases. In this study 220 eligible articles were reviewed. The quality of papers was reviewed based on the researcher-made checklist derived from the Guba and Linck criteria. Results: The findings show that the minimum score earned by articles was 52.33 out of 69.9 and the maximum was 135.18 out of 140. 15% of the articles were of high quality, 52% had a moderate quality and 33% had poor quality. Moreover, the findings also showed credibility at 42%, transferability at 85%, dependability at 54%, and confirmability at 59% of cases were observed. Conclusion: Most of the reviewed phenomenology articles had a moderate quality. Most of the articles were moderate in terms of transferability, dependability and confirmability and were inadequate in terms of credibility.